2011
DOI: 10.1007/s10811-011-9714-z
|View full text |Cite
|
Sign up to set email alerts
|

Lactic acid production from seaweed hydrolysate of Enteromorpha prolifera (Chlorophyta)

Abstract: We examined the feasibility of using the green seaweed Enteromorpha prolifera as an alternative carbon source for chemical production. For this purpose, the chemical composition (proximate analysis, ultimate analysis, and mineral analysis) and acid hydrolysis of E. prolifera were investigated. In addition, lactic acid fermentation of E. prolifera hydrolysate was carried out using five Lactobacillus strains. The lactic acid yield, which is defined as the ratio of the lactic acid production to total sugar consum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 15 publications
1
15
0
Order By: Relevance
“…Fermentation of seaweeds and microalgae (such as Chlorella, Tetraselmis, and Nannochloropsis) led to a lactic acid production (1-5 g L −1 ) comparable to that found in the present study with all tested broths (Gupta et al, 2011;Gupta and Abu-Ghannam, 2012;Uchida and Miyoshi, 2013). Hwang et al (2012) studied the lactic acid fermentation of a hydrolysate prepared from the seaweed Ulva prolifera. In accordance with the results obtained in the present study for SD + S and for SD + S + LAB8014 broths Hwang et al (2012) found that after 24 h of incubation Lactobacillus rhamnosus was able to produce up to 4.3 g L −1 of lactic acid.…”
Section: Suitability Of a Platensis Fandm-c256 Biomass For L Plantarusupporting
confidence: 79%
See 1 more Smart Citation
“…Fermentation of seaweeds and microalgae (such as Chlorella, Tetraselmis, and Nannochloropsis) led to a lactic acid production (1-5 g L −1 ) comparable to that found in the present study with all tested broths (Gupta et al, 2011;Gupta and Abu-Ghannam, 2012;Uchida and Miyoshi, 2013). Hwang et al (2012) studied the lactic acid fermentation of a hydrolysate prepared from the seaweed Ulva prolifera. In accordance with the results obtained in the present study for SD + S and for SD + S + LAB8014 broths Hwang et al (2012) found that after 24 h of incubation Lactobacillus rhamnosus was able to produce up to 4.3 g L −1 of lactic acid.…”
Section: Suitability Of a Platensis Fandm-c256 Biomass For L Plantarusupporting
confidence: 79%
“…Hwang et al (2012) studied the lactic acid fermentation of a hydrolysate prepared from the seaweed Ulva prolifera. In accordance with the results obtained in the present study for SD + S and for SD + S + LAB8014 broths Hwang et al (2012) found that after 24 h of incubation Lactobacillus rhamnosus was able to produce up to 4.3 g L −1 of lactic acid. In the study of Nguyen et al (2012), the microalga Hydrodictyon reticulum was used as substrate for the production of lactic acid by Lactobacillus paracasei LA104.…”
Section: Suitability Of a Platensis Fandm-c256 Biomass For L Plantarumentioning
confidence: 99%
“…Recently, we established the metabolic pathway of 3,6-anhydro-Lgalactose [33], which is one of the main sugar components in Gracilaria, and this would further improve the bioethanol productivity of red seaweeds. Our analysis also indicates U. pertusa would be less useful for the production of L-lactic acid [34,35], whose degree of reductance is 4.0, due to its low degree of reductance compared to other biomass feedstocks. However, U. pertusa would be a fine feedstock for the production of acid products, such as D-glucaric acid (γ = 3.00) and succinic acid (γ = 3.50).…”
Section: Degree Of Reductance Of U Pertusamentioning
confidence: 82%
“…Hwang et al (2012) investigated the lactic acid fermentation of an Ulva (Enteromorpha) prolifera hydrolysate using different Lactobacillus strains. Similar to the present study, the lactic acid produced over 24 h of incubation by L. rhamnosus was 4.3 g L −1…”
Section: Suitability Of a Platensis Fandm-c256 Biomass For L Plantarumentioning
confidence: 99%